Automorphisms of Riemann-Cartan Manifolds with Semi-Symmetric Connection - Panzhensky, V.I. (Журнал математической физики, анализа, геометрии, 2014)
It is proved that the maximum dimension of the Lie group of automorphisms of a Riemann-Cartan manifold (M, g, Ñ̃) is n(n-1)/2, where M is a smooth n-dimensional manifold, g is a Riemannian or semi-Riemannian metric on M, Ñ̃ is a semi-symmetric connection. Доказано, что максимальная размерность группы Ли автоморфизмов многообразия Римана-Картана (M, g, Ñ̃ равна n(n-1)/2 , где M - гладкое n-мерное многообразие, g - риманова или псевдориманова метрика на M, Ñ̃ - полусимметрическая связность.